Economics Teacher Quality: Challenges, and Alternative Development - Sukardi; Muh Fahrurrozi; Baiq Jauziati (IJE : Interdisciplinary Journal of Education, 2023)
The quality of graduates as school’s output is largely determined by many things related to teachers, including economics teachers. At a macro-level, the teacher’s task is related to the development of human resources, which will most determine the sustainability and glory of national life. However, internally the economics teacher is still faced with several problems both concerning the number and qualifications of academic, distribution, and the quality or competence of economics teachers. Besides that, the demands of globalization, changes in the fields of science and technology, economics, socio-political, socio-cultural, and government policies are challenges faced by economic teachers. Minimizing internal problems into strength and anticipating challenges into opportunities is the main strategy to achieve the figure of a professional economics teacher who produce the students who are economically literate, characterized, and have an entrepreneurial spirit. At least four ways are carried out through education, training, experience, and habituation, with religion as the commander.